Case Report: Auditory Hallucination Induced by Amitriptyline for the Treatment of Atypical Odontalgia - Watanabe, Motoko; Nakabayashi, Tetsuo; Nayanar, Gayatri; Takao, Chihiro; Maeda, Chizuko; Tu, Trang Thi Huyen; Motomura, Haruhiko; Toyofuku, Akira (Frontiers in Psychiatry, 2022)
Auditory hallucination is usually associated with psychiatric diseases and organic brain illness. It was rarely found as adverse events of antidepressants. Amitriptyline is considered as one of the first line medications for the psychopharmacotherapy of chronic pain including atypical odontalgia (AO) which shows chronic tooth pain without corresponding abnormalities. Anticholinergic adverse events induced by amitriptyline are usually bearable and not critical since the prescription dose is very low for the patients with AO. This is a first case report about the AO patients who showed auditory hallucination by the low dose of amitriptyline. A 43-years-old female, housewife, complained chronic toothache following dental procedures and was diagnosed as AO. Amitriptyline was initially prescribed 25 mg and gradually increased up to 60 mg with the improvement of AO symptoms in 7 months. Although the temporary recurrence was observed following to the retreatment of prosthodontic dental procedures, it improved in a few weeks. Therefore, the dose of amitriptyline was decreased, and the continuation dose was set 30 mg. In 24 months, the AO symptoms were very much improved; however, she reported that she had been heard the voices at midnight for a year. The voices were neighborhoods' and talking about the noise troubles she had claimed before. She had not realized that the voices were auditory hallucination since they were heard only at midnight infrequent and not bothering her daily life. At the time she reported auditory hallucination, she worried whether organic brain diseases are hiding because the frequency of voices was increased and sometimes occurred in daytime. The adverse event of amitriptyline was suspected since she had never had psychotic symptoms before. Amitriptyline was decreased and continued with the dose of 25 mg. Magnetic resonance imaging and psychiatric consultation revealed no abnormality of brain and in psychiatric aspects. After final prosthodontic treatment, the amitriptyline was discontinued in 30 months. Two months after the discontinuation, auditory hallucination was almost disappeared with no recurrence of AO. The present case report suggests that amitriptyline has possibility to induce auditory hallucination even in conventional dose throughout the treatment of chronic pain including AO.